FEASIBILITY EVALUATION FOR A PREDEFINED SEISMIC RESISTANCE OF STRUCTURES IN UZBEKISTAN (Web of Technology: Multidimensional Research Journal, 2025)
Ensuring adequate seismic resistance in structural design is crucial for minimizing damage and safeguarding human lives, particularly in earthquake-prone regions like Uzbekistan. This review article explores the feasibility of achieving predefined seismic resistance in structures by evaluating current engineering methodologies, material advancements, and regulatory frameworks within the Uzbek context. The study synthesizes research on seismic performance assessment, cost-benefit considerations, and technological innovations in seismic retrofitting and design. Furthermore, it highlights challenges and future directions in achieving optimal seismic resilience specific to Uzbekistan's seismic risk profile and construction practices.